Estratégia de gamification em gestão de projetos de tecnologia da informação - Daniella Fernanda Machado Campos (2016)
The aim of this research describes strategies and procedures used to build a management project platform based on gamification to measure its reflections towards the motivation of a software factory project. The plasticity of human interactions based on intellectual capital boosted the following question: In which proportions the adoption of a strategy for project management based on gamification can change the relationship of a team with its work environment in terms of motivation? This study has a descriptive-quantitative nature and selected two sample groups composed by seventeen individuals. It was concluded that there are no significant evidence to prove the potential of the use of methods based on gamification to change the project team relationship with its work in terms of motivation. This research elucidates the relevance of scientific experiment design for business researches and points to the reliability between the initial proposal and its findings as a means for learning refinement.